The Effect of Job Insecurity, Reward, and Overconfidence Bias on Auditors’ Ethical Decision Making - Ricky Bryan D.P. Tampubolon (Jurnal Akuntansi dan Sistem Informasi, 2026)
Ethical decision making is essential for maintaining audit quality, yet organizational pressures and cognitive biases may undermine auditors’ judgment. This study examines the effects of job insecurity, reward, and overconfidence bias on auditors’ ethical decision making. A cross-sectional survey was conducted with 141 external auditors in Jakarta using five-point Likert scales. Data were analyzed with multiple linear regression. The model was significant (p < .001) and explained 86.2% of the variance in ethical decision making. Job insecurity showed a significant negative effect, reward demonstrated a significant positive effect, and overconfidence bias had a significant negative effect. These findings highlight the importance of reducing perceived job insecurity, implementing fair reward systems, and mitigating overconfidence to strengthen auditors’ ethical behavior and safeguard audit integrity.